Possibilities for development of business cluster network between SMEs from Visegrad countries and Serbia - Mihajlović, Ivan (Serbian Journal of Management, 2014)
This issue of Serbian Journal of Management (SJM 9(2) 2014), besides containing regular research papers, is containing the papers which resulted from the project “Possibilities for development of business cluster network between SMEs from Visegrad countries and Serbia” and the International May Conference on Strategic Management – IMKSM2014 (http://mksm.sjm06.com ). The manuscripts: Entrepreneurs of the Future (Lazani, 2014); The level of process management principles application in SMEs in the selected region of the Czech Republic (Rolinek et al., 2014) and Roles of Socialisation in Strengthening the labour-market positions of young entrants (Marosi, 2014) are the direct result of the Project, which was approved and financially supported by the Visegrad Fund (http://visegradfund.org ), while the manuscript Workspace as a factor of job satisfaction in the banking and ICT industries in Macedonia (Tomovska, et al., 2014) is resulting from the IMKSM2014.